Accidental and Deliberate Self-Poisoning with Medications and Medication Errors among Children in Rural Sri Lanka - Kavinda Dayasiri; S. F. Jayamanne; C. Y. Jayasinghe (Emergency Medicine International)
Context. Pharmaceutical products are the leading cause accidental poisoning in middle- and high-income countries. Patterns of poisoning with medicinal drugs change across different geographic regions and over decades owing to variability in prescription practice, sociocultural factors, safe storage of medicines, and free availability of over the counter medications. Methods. This multicentre descriptive study was conducted over a seven-year period (February 2007 to January 2014) to assess patterns and trends of medicinal drug-related poisoning among children less than 12 years of age in thirty-six hospitals across rural Sri Lanka. Children with both accidental and deliberate medication poisonings and medication errors were recruited to the study. Data on poisoning events and medication errors were gathered via patient/parent interviews using multistructured questionnaires that assessed demographic factors, first aid measures, location and circumstances of poisoning, clinical management, and complications. In addition, focus group discussions were performed on all children and their families who had deliberate poisoning events and medication errors. Results and Conclusions. Among 1621 children presented with acute poisoning over seven years of age, 410 children had acute poisoning with medications. Male children (225, 54.9%) outnumbered female children. Paracetomol (137, 35.6%), salbutamol (55, 14.3%), and chlorpheniramine (35, 9.1%) were the most commonly poisoned medications. Prospective data at Anuradhapura teaching hospital (n = 112) revealed that unsafe first aid measures were practiced on 22 (19.6%) children. Although the majority of children remained asymptomatic (61, 54.5%), neurological symptoms (34, 67%) were predominantly seen in symptomatic children. The majority of poisonings took place within home premises (76, 67.9%). There were 16 reports of medication errors (14.2% of acute poisoning events) either due to erroneous administration by caregivers or erroneous issue of medicines by health workers. The current study did not observe mortality following medication poisonings. This study brings to light the burden of medicinal drug-related poisoning morbidity among children in rural Sri Lanka. Potentially, interventions such as community educational initiatives, written safety warnings, increased use of child resistant containers, and enforcement of laws to bring down accidental medication poisonings need to be implemented, and their effectiveness should be evaluated.